Retrofitting procedures for fatigue-damaged full-scale welded bridge beams. - National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 1978)
"A digest of interim findings from NCHRP Project 12-15(2), "Retrofitting Procedures for Fatigue-Damaged Full-Scale Welded Beams," by John W. Fisher, Fritz Engineering Laboratory, Lehigh University."
Caption title.
At head of title: National Cooperative Highway Research Program.
April 1978.
Keywords: Highway research -- United States